Drum rhythm spaces: From polyphonic similarity to generative maps. Issue 5 (19th October 2020) - Gómez-Marín, Daniel; Jordà, Sergi; Herrera, Perfecto
Abstract : This paper reports on the design and evaluation of drum rhythm spaces as interactive bi-dimensional maps used for the visualisation, retrieval and generation of drum patterns. We carry out two experiments exploring human processing of polyphonic drum patterns concluding with a list of descriptors that significantly influence similarity sensations. These features are used to build spaces based on drum pattern collections, where patterns are organised by similarity, modelled according to human perception. A drum-interpolation algorithm is introduced (and evaluated) to enhance rhythm space functionality by means of patterns that bound it, converting a discrete space to a continuous generative one.